Association of BDNF gene missense polymorphism rs6265 (Val66Met) with three quantitative traits, namely, intelligence quotient, body mass index, and blood pressure: A genetic association analysis from North India - Fatma, Rafat; Chauhan, Waseem; Shahi, Mehdi Hayat; Afzal, Mohammad (Frontiers in Neurology, 2023)
Background: Brain-derived neurotrophic factor (BDNF), a neurotransmitter modulator, plays significant role in neuronal survival, growth and participates in neuronal plasticity, thus, being essential for learning, memory and development of cognition. Additionally, it is crucial in appetite, weight, and metabolic control and have pivotal role in cardiovascular system. The Val66Met polymorphism (rs6265) of BDNF gene causes decrease in BDNF secretion and plays a role in impairments in cognition, energy homeostasis, and cardiovascular events. The aim of the present study was to evaluate the association of polymorphism (rs6265) of BDNF gene with three quantitative traits simultaneously viz: intelligence quotient (IQ), body mass index (BMI) and blood pressure (BP). Methods: Psychometric, morphometric and physio-metric data of the total participants (N=246) were collected. WASI-IIINDIA was used for measurement of the cognitive ability. Genotyping was carried out using allele specific PCR for rs6265 polymorphism (C196T), genotypes were determined. Statistical analyses were performed at p<0.05 significance level using MS-Excel and SigmaPlot. The Odds ratio models with 95% confidence interval were used to test the associations. The used models are co-dominant, recessive, dominant, over dominant and additive. Results: Allelic frequency of allele C and T was 72% and 28%, respectively. Under dominant genetic model, significant susceptible association of minor allele T was observed with below average verbal comprehensive index (OR=2.216, p=0.003, CI (95%) =1.33-3.69), below average performance reasoning index (OR=2.634, p<0.001, CI (95%) =1.573-4.41) and below average full-scale IQ-4 (OR=3.159, p<0.001, CI (95%) =1.873-5.328). Carriers of Met-alleles were found to have increased body mass index (OR=2.538, p<0.001, CI (95%) =1.507-4.275), decreased systolic blood pressure (OR=2.051, p=0.012, CI (95%) =1.202-3.502) and decreased diastolic blood pressure (OR=2.162, p=0.006, CI (95%) =1.278-3.657). Under recessive genetic model, several folds decrease in IQ and BP and increase in BMI with the presence of T allele, were also detected. Conclusions: This novel study may improve our understanding about genetical alterations to the traits and hence be helpful for clinicians and researchers to investigate the diagnostic and prognostic value of this neurotrophic factor.